Developing a model of information security risk assessment based on colored Petri net - Копитін, Юрій Вікторович (Ukrainian Scientific Journal of Information Security, 2014)
The article analyzes the existing models of information security risk assessment as a result of which it is determined that the existing risk assessment models do not sufficiently reflects the structure of the organization, which makes it impossible to obtain a complete information about the risks. Developed a model of information security risk assessment based on colored Petri nets and hypergraphs, which allows you to track the potential harm caused by offenders as a result of threats through the vulnerability of assets and prevented the consequences of threats by used security measures and tools in the specified time. Structured partition of assets to improve the accuracy of their identification is proposed. The results of risk modeling using the proposed model can be used in practice in the phase of information security risks evaluation.